Daun Jambu Biji (Psidium guajava L.) sebagai Antikanker Payudara - Dwitiyanti, Dwitiyanti (Pharmaceutical Sciences and Research, 2015)
Guava leaves are used as a cytotoxic. Previous research has demonstrated that guava leaves contained 61.71% of quersetin and has potential as an cytotoxic. The aim of this study was to determine the cytotoxic activity of 70% ethanol extract of guava leaves against cancer cells T47D. The method used direct counting (viable cell count) to obtained LC50 value. This study used a test solution with six concentrations that were 130.62; 67.98; 35.98; 18.43; 9.56 and 5 µg/ml. The LC50 value from the 70% ethanol extract of guava leaves was 27.54 µg/ml. The results suggested the extract of guava leaves has cytotoxic activity against T47D cells